Micromechanical strength of individual Al2O3 platelets. (1st April 2017) - Feilden, Ezra; Giovannini, Tommaso; Ni, Na; Ferraro, Claudio; Saiz, Eduardo; Vandeperre, Luc; Giuliani, Finn
Abstract: Optimising the properties of platelet reinforced composites requires the strength of the reinforcing phase to be known, however strength measurements at such small scales are difficult and therefore data is sparse. In this work the flexural strength and Weibull modulus of microscopic, alumina platelets has been measured as 5.3 ± 1.3 GPa and 3.7 respectively, using an in-situ micro 3-point bend test. A general approach to correct for the effect of variation in sample size on the Weibull modulus is presented, and the internal structure of the platelets is revealed by TEM. Graphical abstract: